Moderating impact of billboard location and quality on the relationship between advertisement elements and its goals - Ghaiath Altrjman; Asaad Hameed Al-Ali; Raed Ahmad Momni; Khaleel Al-Daoud (Innovative Marketing, 2022)
The study aims to detect the relative impact of the basic advertising elements on attaining advertisement objectives. It also seeks to determine if the location and quality of billboards have an essential moderating impact on the effectiveness of advertising elements concerning their ability to achieve desired advertisement objectives in a developing country such as Jordan.A quantitative survey methodology and an online questionnaire were used to a convenient sample of 450 university students from different academic years and their family members and acquaintances in Amman, Jordan, to achieve the study goals. IBM SPSS version 25 and Smart PLS 3 were used to test the hypotheses. The study revealed a statistically significant impact (p ≤ 0.05) of three billboard advertising elements in achieving the goals of promoting advertisements, namely: headline (t = 3.483), color (t = 2.308), and the number of elements (t = 2.418). However, the study failed to prove the effectiveness of other two elements in achieving these objectives. The analysis did not confirm the effect of moderation of billboard locations and quality between independent variables and billboard’s advertising objectives; however, the location of billboards (independent variable) directly affects the achievement of advertising objectives. The study came up with a set of conclusions, the most important of which is that the billboard still has an important impact on customers’ purchasing behavior or power, regardless of the location and the quality of billboards as a moderator variable.